Thick brane solutions in modified theories of gravity - Dzhunushaliev, V.; Kim, Sung-Won; Nurtayeva, G.K.; Protsenko, N.A.; Idrissov, A. (Recent Contributions to Physics, 2018)
In modern theoretical physics, a number of trends are actively developing, offering a description of cosmological evolution within the framework of extended theories of gravity. Currently, the general state of research is such that it is currently difficult to identify globally preferred areas, and specific approaches have different degrees of development and success. One of their vast areas of modern theoretical physics is the study of modified theories of gravity. Its goal is to find out how gravity can be described within the framework of a modified theory so as not to contradict existing experimental data and offer a better description of a wide range of phenomena in cosmology. Such a program can be implemented from the point of view of problems of quantization of the theory of gravitational interaction. In this article, the thick brane model is considered in the 5-dimensional modified F(r) Rn gravity. It is present regular asymptotically anti-de Sitter solutions contain in some range of value of the parameter n. The main feature of this model consists in existence of a fixed point in phase space where all solutions start and in which is place the brane. Existence of the fixed point allows to avoid thin fine tuning of model parameters for obtaining the studied decisions.